The Implementation of Teaching Writing Using Inquiry Based Method at The Second Grade of MTs Negeri Karangdowo Klaten in 2014/2015 Academic Year - Rahmatun Nisa, Maulida, Mauly Halwat Hikmat, Ph. D, Nur Hidayat S.Pd., M.Pd (2015)
This research aims at describing the Implementation of Teaching Writing using Inquiry based Method at the Second Grade of MTs Negeri Karangdowo Klaten in 2014/2015 Academic Year. This study describes the implementation of teaching writing using inquiry based method and the problems faced by the English teacher in applying this method at the second grade of MTs Negeri Karangdowo Klaten in 2014/2015 academic year. The type of this research is descriptive qualitative. The data obtained are from event, informant, and document. The techniques of collecting data were observation, interview, and document analysis of teaching writing activities to clarify the implementation of teaching writing using inquiry based method and problems faced by the teacher. The result of the analysis shows that the implementation of teaching writing using Inquiry-based method is as follows: 1) Learning objectives of teaching writing at the second grade students of MTs Negeri Karangdowo Klaten are to enable the students in understanding English as mean of communication, and enable the students in being active in practicing English in written form. 2) The teaching materials used by the teacher is taken from some sources based on the syllabus. The teacher used textbook published by Erlangga and students work paper (LKS) as a printed material. The teacher also used other source such as from picture. 3) Teaching procedures used by the teacher are pre-teaching, whilst teaching, and post teaching. Whilst teaching, is divided into orientation, formulate a problem, formulate hypothesis, collecting data, testing hypothesis, and formulate conclusion. 4) The roles of teacher at MTs Negeri Karangdowo Klaten are facilitator, and motivator to the students. 5) The roles of the students in teaching learning process are as an active participant, and as a members of group